Baja California disjunctions and phylogeographic patterns in sympatric California blennies - Bernardi, Giacomo (Frontiers in Ecology and Evolution, 2014)
Baja California disjuncts, which are marine species that are present in the northern Sea of Cortez and along the Pacific Coast of California and Baja California, but absent from the south, have been shown to be interesting models of allopatric speciation. While at least 19 species of fish are Baja California disjuncts, no study has ever evaluated the genetic patterns of closely related species. Here, we used three sympatric California blennies (genus Hypsoblennius), where two species have disjunct populations and one does not. Based on one mitochondrial and one nuclear molecular marker, we found that the two disjunct species exhibit different genetic patterns, one species showing disjunct populations as reciprocally monophyletic assemblages, while the other species showed evidence of gene flow between disjunct populations. In addition, the non-disjunct species, H. gilberti, exhibits high gene flow along the California and Baja California coasts. I hypothesized that adult habitat and historical vicariant events, more so than pelagic larval duration, played major roles in shaping the currently observed distribution and genetic patterns for these species.